2015
DOI: 10.1186/s40248-015-0028-x
|View full text |Cite
|
Sign up to set email alerts
|

8th International conference on management and rehabilitation of chronic respiratory failure: the long summaries – Part 3

Abstract: This paper summarizes the Part 3 of the proceedings of the 8th International Conference on Management and Rehabilitation of Chronic Respiratory Failure, held in Pescara, Italy, on 7 and 8 May, 2015. It summarizes the contributions from numerous experts in the field of chronic respiratory disease and chronic respiratory failure. The outline follows the temporal sequence of presentations.This paper (Part 3) presents a section regarding Moving Across the Spectrum of Care for Long-Term Ventilation (Moving Across t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 128 publications
(148 reference statements)
0
1
0
Order By: Relevance
“…It also remains unclear which Pa co 2 threshold should be used to initiate NIPPV and whether there are clinically significant benefits even with low thresholds. Current guidelines, recommendations, and practices are variable . No trials that performed head-to-head threshold comparisons were identified in this review.…”
Section: Discussionmentioning
confidence: 99%
“…It also remains unclear which Pa co 2 threshold should be used to initiate NIPPV and whether there are clinically significant benefits even with low thresholds. Current guidelines, recommendations, and practices are variable . No trials that performed head-to-head threshold comparisons were identified in this review.…”
Section: Discussionmentioning
confidence: 99%